Familiar felons: gendered characterisations and narrative tropes in media representations of offending women 1905-2015 - Sandman, Tua (Crime, media, culture, 2022)
This article contends that contemporary writings on the representation of offending women provide a simplified outline of ‘available’ representations. To nuance and further complicate our understanding, this study lays bare the most salient media characterisations of women perpetrators in Swedish press. In contrast to much previous research, it covers various offence types and an extensive period of time (1905-2015) and moves away from the focus on mega-cases and cases of extreme deviance. First, the study illustrates that characterisations are contingent and that there is a greater variety in ‘available’ representations than previous research suggests. The characterisations rather tend to move between and beyond the categories of bad, mad and sad. Second, the study makes visible the narrative continuities (across cases and over time) and analyses the social and cultural work of gendered characterisations. While steering attention to sense-making and the construction of familiarity, the article complicates the assumption that women’s deviance primarily or necessarily is represented as otherness.